Comparison of Drugs Prescribed by Psychiatrists and Child/Adolescent Psychiatrists - (:unkn) unknown (AVES, 2020)
Background: Drug utilization patterns may vary between children and adults even for similar indications. Psychiatry is one of the areas where differences of both diagnosis and drug utilization often vary between age groups, imposed by respective separate subspecialties and their prescribing patterns. The study aimed to compare utilization of drugs prescribed by psychiatrists and child/adolescent psychiatrists (CPs). Methods: This study evaluated all electronic prescriptions that were generated by psychiatrists and CPs and registered to the national Prescription Information System in 2016. The drugs in these prescriptions were examined and compared in terms of physician groups. Results: Among 1,150,621 prescriptions generated by psychiatrists and CPs during the study year, 94.2% (n=1,083,631) belonged to psychiatrists and the remaining 5.8% (n=66,990) to CPs. Psychiatrists were detected to prescribe significantly fewer nervous system drugs than CPs did (89.5% vs. 97.8%, p<0.001). Antidepressants constituted 57.4% of all nervous system drugs prescribed by psychiatrists, which was significantly lower in the prescriptions of CPs as 22.1% (p<0.001). Within antidepressants, SSRIs were significantly more preferred by CPs (91.4%) than that by psychiatrists (56.2%), (p<0.001). Centrally-acting sympathomimetics formed 46.6% of nervous system drugs prescribed by CPs compared to 2.4% of that by psychiatrists (p<0.001). Among these sympathomimetics, methylphenidate was the most commonly preferred drug by both CPs and psychiatrists (%84.6% vs. %68.6, respectively; p<0.001). Conclusions: It seems that centrally-acting sympathomimetics constitute near half of the drugs preferred by CPs who tend to prescribe a limited number of different drugs. Contrarily, psychiatrists tend to prescribe wide spectrum of drugs, half of these being antidepressants. The study highlights some discrepancies of psychotropic drug use regarding approved indication and clinical practice for different age groups.
Keywords: drug prescribing; psychiatry; child health; serotonin and noradrenaline reuptake inhibitors; antidepressive agents; methylphenidate; ATTENTION DEFICIT/HYPERACTIVITY DISORDER; MAJOR DEPRESSIVE DISORDER; MENTAL-HEALTH-SERVICES; 5 WESTERN COUNTRIES; CHILDREN; TRENDS; PREVALENCE; MEDICATION; PATTERNS; ADOLESCENTS